Essential oil-water emulsions containing a biosurfactant from Lactobacillus paracasei - Vecino, Xanel (2016)
[Excerpt] Surfactants play important roles in cosmetic products due to diverse properties including as emulsifier, foaming, wetting, detergency and solubilizer agents, among others. However, the market for beauty and personal care products based on natural ingredients has shown a relevant growth. In this sense, biosurfactants being non-toxic, biodegradable and ecofriendly natural compounds are suitable replacers of the chemical-based surfactants showing equal or better performances [1]. In addition, essential oils are natural ingredients extracted from plants that also are interesting ingredients for novel cosmetic formulations.The aim of this study was to formulate oil-water emulsions using a biosurfactant from Lactobacil/us paracasei in combination with several essential oils (wheat germ, almond, rosemary and jojoba oil). [...]